Universal birth registration as a catalytic children’s development tool [Sierra Leone] - Hanciles, Cecilia; Wilson, Ralph; Massaquoi, Paul (Technical Centre for Agricultural and Rural Cooperation, 2018)
To improve the rights of unregistered children and young people in Sierra Leone, Plan International has developed a birth registration tool to enable age and identity verification for this vulnerable group. Today, the young participants of the project are accessing their age-appropriate privileges, such as being able to attend school and getting to vote.